2013
DOI: 10.1073/pnas.1302547110
|View full text |Cite
|
Sign up to set email alerts
|

Concepts and implications of altruism bias and pathological altruism

Abstract: The profound benefits of altruism in modern society are self-evident. However, the potential hurtful aspects of altruism have gone largely unrecognized in scientific inquiry. This is despite the fact that virtually all forms of altruism are associated with tradeoffs-some of enormous importance and sensitivity-and notwithstanding that examples of pathologies of altruism abound. Presented here are the mechanistic bases and potential ramifications of pathological altruism, that is, altruism in which attempts to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 75 publications
(54 reference statements)
1
32
0
3
Order By: Relevance
“…Of the two charities presented to participants, one was objectively better at achieving its outcomes but less well-known, whereas the other was objectively worse but more popular. If sufficiently high, empathy might lead to "pathological" or maladaptive altruism: pro-social behavior that is ineffective or even counter-productive (Oakley, 2013). One study found that a physiological response linked to pro-sociality (i.e., vagal nerve activity), if sufficiently high, can interfere with pro-social behavior (Kogan et al, 2014).…”
Section: Experiments 4: Unintentional Empathy Associates With Donationmentioning
confidence: 99%
“…Of the two charities presented to participants, one was objectively better at achieving its outcomes but less well-known, whereas the other was objectively worse but more popular. If sufficiently high, empathy might lead to "pathological" or maladaptive altruism: pro-social behavior that is ineffective or even counter-productive (Oakley, 2013). One study found that a physiological response linked to pro-sociality (i.e., vagal nerve activity), if sufficiently high, can interfere with pro-social behavior (Kogan et al, 2014).…”
Section: Experiments 4: Unintentional Empathy Associates With Donationmentioning
confidence: 99%
“…Of the two charities presented to participants, one was objectively better at achieving its outcomes but less well-known, whereas the other was objectively worse but more popular. If sufficiently high, empathy might lead to "pathological" or maladaptive altruism: pro-social behavior that is ineffective or even counter-productive (Oakley, 2013). One study found that a physiological response linked to pro-sociality (i.e., vagal nerve activity), if sufficiently high, can interfere with pro-social behavior (Kogan et al, 2014).…”
Section: Experiments 4: Unintentional Empathy Associates With Donationmentioning
confidence: 99%
“…A perceiver might misunderstand the goal a target is trying to pursue, or the means of goal pursuit, or the target's own understanding of goal progress. Mistaking any of these aspects of another person's goal pursuit could produce maladaptive empathy, in the sense of being suboptimal or harmful to the target (Oakley, 2013).…”
Section: The Target's Goalsmentioning
confidence: 99%